Evolution of Brain-Expressed Biogenic Amine Receptors into Olfactory Trace Amine-Associated Receptors. (11th January 2022) - Guo, Lingna; Dai, Wenxuan; Xu, Zhengrong; Liang, Qiaoyi; Miller, Eliot T; Li, Shengju; Gao, Xia; Baldwin, Maude W; Chai, Renjie; Li, Qian
Abstract: The family of trace amine-associated receptors (TAARs) is distantly related to G protein-coupled biogenic aminergic receptors. TAARs are found in the brain as well as in the olfactory epithelium where they detect biogenic amines. However, the functional relationship of receptors from distinct TAAR subfamilies and in different species is still uncertain. Here, we perform a thorough phylogenetic analysis of 702 TAAR-like (TARL) and TAAR sequences from 48 species. We show that a clade of Tarl genes has greatly expanded in lampreys, whereas the other Tarl clade consists of only one or two orthologs in jawed vertebrates and is lost in amniotes. We also identify two small clades of Taar genes in sharks related to the remaining Taar genes in bony vertebrates, which are divided into four major clades. We further identify ligands for 61 orphan TARLs and TAARs from sea lamprey, shark, ray-finned fishes, and mammals, as well as novel ligands for two 5-hydroxytryptamine receptor 4 orthologs, a serotonin receptor subtype closely related to TAARs. Our results reveal a pattern of functional convergence and segregation: TARLs from sea lamprey and bony vertebrate olfactory TAARs underwent independent expansions to function as chemosensory receptors, whereas TARLs from jawed vertebrates retain ancestral response profiles and may have similar functions to TAAR1 in the brain. Overall, our data provide a comprehensive understanding of the evolution and ligand recognition profiles of TAARs and TARLs.